2012
DOI: 10.1007/s10546-012-9751-4
|View full text |Cite
|
Sign up to set email alerts
|

Wind-Turbine Wakes in a Convective Boundary Layer: A Wind-Tunnel Study

Abstract: Thermal stability changes the properties of the turbulent atmospheric boundary layer, and in turn affects the behaviour of wind-turbine wakes. To better understand the effects of thermal stability on the wind-turbine wake structure, wind-tunnel experiments were carried out with a simulated convective boundary layer (CBL) and a neutral boundary layer. The CBL was generated by cooling the airflow to 12-15 • C and heating up the test section floor to 73-75 • C. The freestream wind speed was set at about 2.5 m s −… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
70
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(86 citation statements)
references
References 34 publications
14
70
0
Order By: Relevance
“…On the other hand, no signature of the tip vortex remains visible at x/D = 3, even for the low turbulent inflow conditions. These results are consistent with Zhang et al [23,24] works. They showed that the tip vortex signatures are not distinguishable anymore from x/D = 3 in a neutral or convective incoming boundary layer with a turbulence intensity of 8% at hub height.…”
Section: Tip-vortex Signature Persistencesupporting
confidence: 94%
See 1 more Smart Citation
“…On the other hand, no signature of the tip vortex remains visible at x/D = 3, even for the low turbulent inflow conditions. These results are consistent with Zhang et al [23,24] works. They showed that the tip vortex signatures are not distinguishable anymore from x/D = 3 in a neutral or convective incoming boundary layer with a turbulence intensity of 8% at hub height.…”
Section: Tip-vortex Signature Persistencesupporting
confidence: 94%
“…The values of maximum velocity deficit (40 to 50% of the mean hub velocity) are representative of full scale wind turbine wakes and are in agreement with literature [21,24,22]. Since the wake diffusion is dependent of the boundary layer conditions, it is difficult de precisely compare the wake evolution obtained in the latter references.…”
Section: Experimental Set-upsupporting
confidence: 85%
“…This behavior was reported in previous numerical and experimental studies by Wu and Porté-Agel 40 , Rados et al 41 , Chamorro and Porté-Agel 42 , and Zhang et al 10 . Recently, Bastankhah and Porté-Agel 17 developed a new analytical model to predict the wind velocity distribution downwind of a wind turbine by applying conservation of mass and momentum and assuming a self-similar Gaussian distribution for the velocity deficit in the wake.…”
Section: B Analytical Wake Modelingsupporting
confidence: 85%
“…They showed that the wakes recover faster under the convective conditions compared with the neutral cases. Recently, Zhang et al 10 carried out wind-tunnel experiments of the down-scaled wind-turbine models to investigate the effect of thermal stability on wind-turbine wakes under the convective and neutral conditions. They found a smaller velocity deficit (around 15% at the wake center) in the CBL compared with the wake of the same wind turbine in the neutral boundary layer.…”
Section: Introductionmentioning
confidence: 99%
“…There are experimental studies considering different atmospheric stratifications (NBL, SBL, CBL) (e.g. Medici and Alfredsson (2006), Chamorro and Porté-Agel (2010), Zhang et al (2012), Tian et al (2013), Zhang et al (2013)). In most of the numerical simulations of an individual wind turbine, however, an NBL is assumed (e.g.…”
mentioning
confidence: 99%